Hydrogen Repairs LPS-Induced Endothelial Progenitor Cells Injury via PI3K/AKT/eNOS Pathway - Mu, Qingjie; Lv, Kaixuan; Yu, Jielun; Chu, Shangmin; Zhang, Lichun; Kong, Lingyu; Zhang, Linlin; Tian, Yan; Jia, Xiaopeng; Liu, Benhong; Wei, Youzhen; Yang, Nana (Frontiers in Pharmacology, 2022)
Endotoxins and other harmful substances may cause an increase in permeability in endothelial cells (ECs) monolayers, as well as ECs shrinkage and death to induce lung damage. Lipopolysaccharide (LPS) can impair endothelial progenitor cells (EPCs) functions, including proliferation, migration, and tube formation. EPCs can migrate to the damaged area, differentiate into ECs, and participate in vascular repair, which improves pulmonary capillary endothelial dysfunction and maintains the integrity of the endothelial barrier. Hydrogen (H2) contributes to the repairment of lung injury and the damage of ECs. We therefore speculate that H2 protects the EPCs against LPS-induced damage, and it‘s mechanism will be explored. The bone marrow-derived EPCs from ICR Mice were treated with LPS to establish a damaged model. Then EPCs were incubated with H2, and treated with PI3K inhibitor LY294002 and endothelial nitric oxide synthase (eNOS) inhibitor L-NAME. MTT assay, transwell assay and tube formation assay were used to detect the proliferation, migration and angiogenesis of EPCs. The expression levels of target proteins were detected by Western blot. Results found that H2 repaired EPCs proliferation, migration and tube formation functions damaged by LPS. LY294002 and L-NAME significantly inhibited the repaired effect of H2 on LPS-induced dysfunctions of EPCs. H2 also restored levels of phosphor-AKT (p-AKT), eNOS and phosphor-eNOS (p-eNOS) suppressed by LPS. LY294002 significantly inhibited the increase of p-AKT and eNOS and p-eNOS expression exposed by H2. L-NAME significantly inhibited the increase of eNOS and p-eNOS expression induced by H2. H2 repairs the dysfunctions of EPCs induced by LPS, which is mediated by PI3K/AKT/eNOS signaling pathway.